Mid-range left ventricular ejection fraction: Clinical profile and cause of death in ambulatory patients with chronic heart failure. (1st August 2017) - Pascual-Figal, Domingo A.; Ferrero-Gregori, Andreu; Gomez-Otero, Ines; Vazquez, Rafael; Delgado-Jimenez, Juan; Alvarez-Garcia, Jesus; Gimeno-Blanes, Juan R.; Worner-Diz, Fernando; Bardají, Alfredo; Alonso-Pulpon, Luis; Gonzalez-Juanatey, Jose Ramon; Cinca, Juan; et al.
Abstract: Background: The intermediate group of patients with heart failure (HF) and mid-range left ventricular ejection fraction (HFmrEF) may constitute a specific phenotype, but a direct evidence is lacking. This study aimed to know whether this HF category is accompanied by a particular clinical phenotype and prognosis. Methods and results: This study includes 3446 ambulatory patients with chronic HF from two national registries. According to EF at enrollment, patients were classified as reduced (HFrEF, < 40%), mid-range (HFmrEF, 40–49%) or preserved (HFpEF, ≥ 50%). Patients were followed-up for a median of 41 months and the specific cause of death was prospectively registered. Patients with HFmrEF represented 13% of population and they exhibited a phenotype closer to HFrEF, except for a higher rate of coronary revascularization and diabetes, and a less advanced HF syndrome. The observed all-cause mortality was higher among HFrEF (33.0%), and similar between HFmrEF (27.8%) and HFpEF (28.0%) (p = 0.012); however, the contribution of each cause of death differed significantly between categories (p < 0.001). After propensity score matching, the risk of cardiovascular death, HF death or sudden cardiac death did not differ between HFmrEF and HFrEF in paired samples; however, patients with HFmrEF were at higher risk of cardiovascular death (sHR 1.71, 95% CI 1.13–2.57, p = 0.011) and sudden cardiac death (sHR 2.73, 95% CI 1.07–6.98, p = 0.036) than patients with HFpEF. Conclusions: Patients in the intermediate category of HFmrEF conform a phenotype closer to the clinical profile of HFrEF, and associated to higher risk of sudden cardiac death and cardiovascular death than patients with HFpEF.